Development and evaluation of a new procedure for subject-specific tensioning of finite element knee ligaments. Issue 11 (8th September 2021) - Lahkar, Bhrigu K.; Rohan, Pierre-Yves; Pillet, Helene; Thoreux, Patricia; Skalli, Wafa
Abstract: Subject-specific tensioning of ligaments is essential for the stability of the knee joint and represents a challenging aspect in the development of finite element models. We aimed to introduce and evaluate a new procedure for the quantification of ligament prestrains from biplanar X-ray and CT data. Subject-specific model evaluation was performed by comparing predicted femorotibial kinematics with the in vitro response of six cadaveric specimens. The differences obtained using personalized models were comparable to those reported in similar studies in the literature. This study is the first step toward the use of simplified, personalized knee FE models in clinical context such as ligament balancing.